Твердофазне спектрофотометричне визначення іонів металів у варених ковбасах - Костенко, Єлизавета Євгеніївна (My University, 2012)
Запропонована схема твердофазного спектрофотометричного визначення іонів Cu (II), Zn (II), Pb (II), Cd (II), Hg (II), Fe (III) з використанням азо- і сульфофталеїнових барвників, іммобілізованих на аніонообміннику АВ-17-8 у зразках ковбасних виробів. The Offered scheme interface spectrophotometric of the determination ion Cu (II), Pb (II), Zn (II), Cd (II), Hg (II), Fe (III) in sample of the boiled sausages with use immobilized on anionite AB-17-8 dye staffs: acid chromiumdarkblue, SPADNS, xilenolov orange, pirokhatekhin violet, hromazurol S. The Used methodses of the determination ion metal are characterized by satisfactory correctness and repeatability result; high sensitivity and selection; on velocity they exceed known similar and standard methodses at condition of the use the ultrasound for preparing the tests and speedups of the determination of the balance in differentphase systems. The Scheme is characterized by simplicity of the experiment, ecological safety does not require complex high-priced equipment, for servicing which necessary high skilled personnel and stationary laboratory. On result of the determination ion Cu (II), Pb (II), Zn (II), Cd (II), Hg (II), Fe (III) is installed that all sample of the boiled sausages are an ecological safety.
Keywords: твердофазна спектрофотометрія; іммобілізовані на іонообміннику барвники; харчові продукти; фотометричний аналіз; interface spectrophotometric; immobilized on the surface of ionite of the dye staffs; foodstuffs; photometric analysis; кафедра харчової хімії